Youth in Post-Apartheid South Africa - Amoateng, Acheampong; Biney, Elizabeth (Taylor & Francis, 2024)
This book investigates the life experiences of youth in South Africa, considering whether contemporary youth have benefitted from the socioeconomic reconstruction of post-apartheid society.